All‐Solid‐State Double‐Layer Capacitors Using Binderless Reduced Graphene Oxide Thin Films Prepared by Bipolar Electrochemistry. Issue 8 (1st June 2017) - Allagui, Anis; Ashraf, Juveiriah Mohammed; Khalil, Malathe; Abdelkareem, Mohammad Ali; Elwakil, Ahmed S.; Alawadhi, Hussain
Abstract: Bipolar electrochemistry is used as an economical, single‐step, and scalable process for the oxidation of a wireless graphite substrate, and the subsequent electrophoretic deposition of graphene oxide thin film on a second wireless substrate. An all‐solid‐state symmetric double‐layer capacitor (EDLC) using binderless reduced graphene oxide electrodes exhibited outstanding reversibility and capacitance retention over 18000 cycles, as well as superior capacitive behavior at far‐from‐dc frequencies (for example 45 and 47  μ F cm - 2 ), effective capacitances at 75 and 189 Hz, respectively (computed using a series resonance network with ideal inductors), compared to 55  μ F cm - 2 at close‐to‐dc (computed from cyclic voltammetry at 10 mV s - 1 ). This makes the device well‐suited for ac filtering applications. A one‐hour thermal treatment of the electrodes at 900 °C under vacuum increased the capacitance 13‐fold (719  μ F cm - 2 ) at close‐to‐dc, which decreased to 185 and 150  μ F cm - 2 as the frequency was increased to 37 and 106 Hz, respectively These properties make this device suitable for both reasonable dc energy storage and higher frequency applications. Abstract : Energy storage : All‐solid‐state symmetric double‐layer capacitors (EDLCs) using binderless, reduced graphene oxide (rGO) thin films prepared by bipolar electrochemistry show excellent capacitive behavior at low and high frequencies, making the devices suitable for dc energy storage as well as ac line filtering applications.